2023
DOI: 10.3324/haematol.2023.282866
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine biosynthesis is a targetable metabolic vulnerability in multiple myeloma

Abstract: Multiple Myeloma (MM) is the second most prevalent hematological malignancy and is incurable due to the inevitable development of drug resistance. The methionine adenosyltransferase 2α (MAT2A) is the primary producer of the methyl donor S-adenosylmethionine (SAM) and several studies reported MAT2A deregulation in different solid cancers. As the role of MAT2A in MM is not studied yet, the aim of this study was to clarify the potential role and underlying molecular mechanisms of MAT2A in MM, exploring new therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Further analysis demonstrated that PYCR1 inhibition also reduced cellular uptake of puromycin, confirming that protein synthesis was inhibited [ 102 ]. Similarly, MAT2A inhibition also inactivated the mTOR-4E-BP1 pathway, accompanied with a decrease in protein synthesis, again resulting in MM cell death [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis demonstrated that PYCR1 inhibition also reduced cellular uptake of puromycin, confirming that protein synthesis was inhibited [ 102 ]. Similarly, MAT2A inhibition also inactivated the mTOR-4E-BP1 pathway, accompanied with a decrease in protein synthesis, again resulting in MM cell death [ 104 ].…”
Section: Introductionmentioning
confidence: 99%